Knowledge and Precaution. On Organic Farmers Assessment of New Technology. Issue 2 (28th December 2016) - Lassen, Jesper; Oelofse, Myles
Abstract: Organic farming is under constant pressure to reinvent itself by adopting new technologies. This article examines the role of precaution in organic farmers' assessments of new technologies, and asks how their assessments draw on different types of knowledge. The article further explores how knowledge type compares to the role of knowledge and precaution expressed in the principles of organic farming as defined by the organic movement organisation, IFOAM. Results from a study of the introduction of sewage sludge as an alternative source of nutrients in organic agriculture are presented. Empirically, this case‐study builds on the analysis of five focus groups made up of Danish organic farmers. While some farmers called for precaution, supporting this with claims about lacking knowledge, others trusted the authorities and accepted sewage sludge provided it was officially approved for organic use. Our analysis suggests that when assessing new technologies Danish organic farmers rely on scientific knowledge and do not automatically draw on the experiential knowledge they possess and employ in other contexts. It is concluded that if IFOAM wishes include farmers' experiential knowledge as a basis for decisions about precaution, there is a need to develop instruments making it possible to tap into this knowledge.